Diversity of soils in areas with the presence of Furcraea sp. in tropical ecosystems - Medina-Cano, Clara Inés; Vásquez-Gallo, Luz Adriana; Tamayo-Vélez, Álvaro de Jesús; Vargas-Arcila, María; Henao-Rojas, Juan Camilo (Agronomía Mesoamericana, 2022)
Introduction. The fique, “cabuya” or “mecate” are the common names given to the species of the genus Furcraea that are used for the manufacture of biodegradable fibers. Their industrial and social importance in Latin American countries is significant since it is usually related to family and peasant economies. However, for this taxonomic group, the diversity of edaphic conditions in natural habitats or cultivation sites is unknown. Objective. To physicochemically characterize the soils in the productive systems and natural populations of fique, to determine the aspects and factors that best represent their variability. Materials and methods. The work was developed between 2013 and 2014, in 66 municipalities and 108 villages in 11 departments of Colombia. Passport data was recorded at the 121 sites visited, describing site conditions, including georeferencing. In each locality, soil samples were taken in the first 20 cm of depth and subsequently the following variables were determined: texture, pH, organic matter (OM), P, S, K, Mg, Ca, Al+H, CE, cations of change Ca, Mg, K, Na, cationic exchange capacity (ECEC), Ca, Mg, K, and Na. According to georeferencing, 52 agroecological zones were identified. Results. Populations located between 170 to 2,993 m.a.s.l. were found. The most significant factors were agroecological zone and soil texture. Among them, texture was the factor with the greatest capacity for group formation and represented 60.99 % of the variability of the sampled soils. The variables that most contribute to the variability of the soils were (Ca + Mg) / K, exchangeable Mg, K / Mg, exchangeable Ca, and ECEC. Conclusion. The results obtained for wild and cultivated populations indicate that the different taxa survive in diverse tropical soil conditions. It was found that the exchangeable ions had high discriminating power that could indicate diversity to the different conditions and fertility levels of Colombian soils.